Deoxycholate‐Based Glycosides (DCGs) for Membrane Protein Stabilisation. Issue 10 (7th May 2015) - Bae, Hyoung Eun; Gotfryd, Kamil; Thomas, Jennifer; Hussain, Hazrat; Ehsan, Muhammad; Go, Juyeon; Loland, Claus J.; Byrne, Bernadette; Chae, Pil Seok
Abstract Detergents are an absolute requirement for studying the structure of membrane proteins. However, many conventional detergents fail to stabilise denaturation‐sensitive membrane proteins, such as eukaryotic proteins and membrane protein complexes. New amphipathic agents with enhanced efficacy in stabilising membrane proteins will be helpful in overcoming the barriers to studying membrane protein structures. We have prepared a number of deoxycholate‐based amphiphiles with carbohydrate head groups, designated deoxycholate‐based glycosides (DCGs). These DCGs are the hydrophilic variants of previously reported deoxycholate‐based N‐oxides (DCAOs). Membrane proteins in these agents, particularly the branched diglucoside‐bearing amphiphiles DCG‐1 and DCG‐2, displayed favourable behaviour compared to previously reported parent compounds (DCAOs) and conventional detergents (LDAO and DDM). Given their excellent properties, these agents should have significant potential for membrane protein studies.